THE ENZYMES OF SOME ELASMOBRANCHS FROM BOMBAY. I. PROTEASES - Ghanekar, D S; Bal, D V (Indian Journal of Fisheries, 2016)
AT present a large amount of data on the enzymes of various tissues of higheranimals, plants, yeasts, molds and bacteria is available. However, nodetailed study of the enzymes of fish has been reported in the literatureexcept the crystallization of salmon pepsin (Norris and Elam, 1940) andinvestigations on shark gastric proteinase (Sprissler, 1942) smd shark pancreaticproteinase (Boos, 1943).